Decline in Medicare Utilization and Reimbursement Rates in Ophthalmic Plastic and Reconstructive Surgery: 2010–2019. Issue 1 (January 2022) - Gong, Jung Ho; Khurana, Aditya; Eltorai, Adam E. M.; Wagner, Lilly H.
Abstract : Background: Analysis of current and past reimbursement patterns for federally funded programs is crucial to develop sustainable future payment models. Methods: The Centers for Medicare and Medicaid Services Physician Fee Schedule was used to evaluate 26 common ophthalmic plastic and reconstructive surgery (OPRS) procedures. From 2010 to 2019, compound annual growth rate, total percent change, and annual percent change were calculated using inflation-adjusted reimbursement rates. Centers for Medicare and Medicaid Services' Physician/Supplier Procedure Summary was used to assess the surgical volume of the 26 procedures in ophthalmology and plastic surgery services. Results: From 2010 to 2019, total billed surgical procedures in OPRS decreased by 57.0%, affecting both ophthalmologists (−54.3%) and plastic surgeons (−80.1%). Over the study period, inflation-adjusted reimbursement rates decreased by 5.6%. Compound annual growth rate was −0.66%, and annual percent change was −0.62%. From 2010 to 2013, reimbursement rates increased by 1.8% each year. In contrast, from 2013 to 2019, reimbursement rates decreased by 1.7% each year ( P < 0.0001). Conclusions: From 2010 to 2019, Medicare utilization has substantially declined for OPRS procedures. Inflation-adjusted Medicare reimbursement rates have decreased for the majority of common procedures since 2013. Surgeons and policymakers need to be aware of these trends to ensure future availability of subspecialty surgical services.